Effectiveness of patients’ involvement in a medical and nursing pain education programme: a protocol for an open-label randomised controlled trial including qualitative data - Francesca Rossi; Roberto D'Amico; Alice Serafini; Luca Ghirotto; Matías Eduardo Díaz Crescitelli; Maria Grazia Rossi; Sara Alberti; Erika Borellini; Annamaria Contini; Simone Cernesi; Paola Ferri; Davide Fornaciari; et al. (BMJ Open, 2024)
Introduction Pain is a multidimensional experience that varies among individuals and has a significant impact on their health. A biopsychosocial approach is recommended for effective pain management; however, health professionals’ education is weak on this issue. Patient involvement is a promising didactic methodology in developing a more holistic perspective, however there is a lack of reliable evidence on this topic. The aim of the present study is to evaluate the effectiveness of patient involvement in pain education in undergraduate medicine and nursing students.Methods and analysis An open-label randomised controlled trial including qualitative data will be conducted. After an introductory lesson, each student will be randomly assigned to the intervention group, which includes an educational session conducted by a patient–partner along with an educator, or to the control group in which the session is exclusively conducted by an educator. Both sessions will be carried out according to the Case-Based Learning approach. Primary outcomes will be students’ knowledge, attitudes, opinions and beliefs about pain management, whereas the secondary outcome will be students’ satisfaction. The Pain Knowledge and Attitudes (PAK) and Chronic Pain Myth Scale (CPMS) will be administered preintervention and postintervention to measure primary outcomes. Students’ satisfaction will be measured by a questionnaire at the end of the session. Two focus groups will be conducted to evaluate non-quantifiable aspects of learning.Ethics and dissemination The protocol of this study was approved by the independent Area Vasta Emilia Nord ethics committee.Adherence to The Declaration of Helsinki and Good Clinical Practice will ensure that the rights, safety and well-being of the participants in the study are safeguarded, as well as data reliability. The results will be disseminated through scientific publications and used to improve the educational offer. A version of the anonymised data set will be released for public access.Trial registration Trial was not registered on ClinicalTrials.gov as the interventions being compared only concern educational programmes and the outcomes considered do not refer to any clinical dimension.